Arctic Gakkel Vents (AGAVE) 2007 - Meteorological, Oceanographic and Ship Data Collected Onboard Icebreaker Oden - Swedish Polar Research Secretariat (Swedish Polar Research Secretariat, 2017)
AGAVE was a US-financed project where scientists explored life in the hydrothermal vents from the core of the Earth, which has been found at the Gakkel Ridge, a mountain ridge below the Arctic Ocean.

The expedition was an International Polar Year (IPY) collaboration between scientists from the USA, Sweden, Germany and Japan.

The AGAVE expedition made a number of exciting discoveries on the Gakkel Ridge, and one of the most surprising was the fact that the axial valley at the 85°E segment is blanketed in pyroclastic deposits - the largest unconsolidated deposits ever found on the seafloor (picture 4). These deposits are caused by explosive volcanic eruptions, which many scientists had assumed were impossible in the deep ocean because of the great pressures at such depths. The AGAVE observations turn this idea upside down, and demonstrate that volcanic activity at the 85°E site has been accompanied by the catastrophic discharge of magmatic volatiles. These pyroclastic deposits are being analyzed to determine their age and composition in order to better understand this surprising result. The deposits were found around a previously unknown chain of volcanoes, which were named the Asgard Chain - Oden, Thor, and Loke, in honor of the outstanding scientific support provided by the officers and crew of IB Oden.

Purpose:

The AGAVE expedition had two sets of complimentary objectives. The scientific objective was to study the geological, chemical, and biological characteristics of volcanic activity and hydrothermal venting on the Gakkel Ridge. The engineering objective was to develop new technologies for deep-sea research in ice-covered oceans.

This data set contains meteorological, oceanographic and ship data collected during the US-Swedish expedition Arctic Gakkel Vents (AGAVE), which was an international research cruise using the icebreaker Oden in the Arctic Ocean.

Data includes:

meteorological variables: Air temperature, Humidity, Wind direction/speed, Atmospheric pressure.

Oceanographic variables: Sea water temperature, Conductivity, Salinity and Sound velocity.

Ship data: Position, Speed, Course, Water depth.

Further metadata on instrumentation and the individual variables can be found in the info file. Graphics and files describing the route are included in the package.

Quality Information:

Obviously erroneous data (e.g. negative air pressure) have been omitted. No other processing or quality check of the data has been undertaken. Users should be aware of this in further data handling and analysis.

I juli 2007 genomfördes forskningsexpeditionen Arctic Gakkel Vents (AGAVE) med isbrytaren Oden i Arktiska oceanen. AGAVE var ett amerikanskt forskningsprojekt där man undersökte livet i de hydrotermala utlopp från jordens kärna man har hittat vid Gakkelryggen, en bergsrygg under Arktiska oceanen.

Expeditionen genomfördes i samarbete mellan forskare från USA, Sverige, Tyskland och Japan inom ramen för det Internationella polaråret 2007–2008.

Under AGAVE-expeditionen gjordes en mängd upptäckter, men den största är nog att axialklyftan vid 85°E på Gakkelryggen är täckt av pyroklastiska avlagringar (material från vulkanutbrott), och det är den största enskilda pyroklastiska avlagringen som någonsin hittats på havsbotten.

Syfte:

AGAVE-expeditionen hade två syften: ett vetenskapligt syfte som var att undersöka Gakkelryggens vulkaniska och hydrotermiska egenskaper, samt ett tekniskt syfte som var att utveckla ny teknik för forskning av istäckta hav.

This data set contains meteorological, oceanographic and ship data collected during the US-Swedish expedition Arctic Gakkel Vents (AGAVE), which was an international research cruise using the icebreaker Oden in the Arctic Ocean.

Data includes:

meteorological variables: Air temperature, Humidity, Wind direction/speed, Atmospheric pressure.

Oceanographic variables: Sea water temperature, Conductivity, Salinity and Sound velocity.

Ship data: Position, Speed, Course, Water depth.

Further metadata on instrumentation and the individual variables can be found in the info file. Graphics and files describing the route are included in the package.

Quality Information:

Obviously erroneous data (e.g. negative air pressure) have been omitted. No other processing or quality check of the data has been undertaken. Users should be aware of this in further data handling and analysis.
Arctic Gakkel Vents (AGAVE) 2007 - Meteorologiska och oceanografiska data, samt skeppsdata, insamlade ombord på isbrytaren Oden - Arctic Gakkel Vents (AGAVE) Expedition - Meteorological, Oceanographic and Ship Data Collected Onboard Icebreaker Oden during July 1 through August 9 2007
Keywords: Meteorology; Meteorologi; ATMOSPHERE; ATMOSPHERIC WINDS; SURFACE WINDS; ATMOSPHERIC TEMPERATURE; ATMOSPHERIC WATER VAPOR; HUMIDITY; ATMOSPHERIC PRESSURE; SURFACE PRESSURE; OCEANS; SALINITY; CONDUCTIVITY; DENSITY; OCEAN TEMPERATURE; WATER TEMPERATURE; WATER DEPTH; SEAFLOOR TOPOGRAPHY; BATHYMETRY; The icebreaker Oden; Isbrytaren Oden; Environmental Sciences; Miljövetenskap; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser; Engineering and Technology; Teknik; Climatology / Meteorology / Atmosphere; Klimatologi och meteorologi; Oceans; Kust och hav